Peran Artificial Intelligence dalam Rekrutmen dan Seleksi: Meningkatkan Efisiensi dan Akurasi dalam MSDM - Efrita Norman; Enah Pahlawati (MES Bogor, 2024)
Artificial Intelligence (AI) has become an important element in various aspects of life, including Human Resource Management (HRM). AI offers great potential to increase efficiency and accuracy in employee recruitment and selection processes. This research aims to explore how AI can be implemented in recruitment and selection to increase the speed, effectiveness and fairness of the process. This research also evaluates the benefits and challenges faced in using AI in the HRM context, with a particular focus on the candidate screening process based on relevant criteria. The research approach used is a literature study, where data is collected from books, journal articles, industry reports, and other reliable sources. The literature review includes analysis of a variety of academic and practical sources relevant to this topic, to gain a comprehensive picture of the development and application of AI in recruitment and selection. The analysis process involves identifying key themes related to adaptive and flexible leadership and their implications for organizations . This method was chosen to gain a comprehensive understanding of the concepts discussed and their relevance in the context of digital transformation. The research results show that the use of AI in recruitment and selection can significantly increase the efficiency and speed of candidate screening. AI is able to automate the resume screening process, perform big data analysis, and use natural language processing to interact with candidates in a more personal way. AI systems are also able to reduce subjective bias, increase objectivity in decision making, and enable significant time and cost savings. Additionally, the study found that customization of screening criteria provided by AI allows companies to tailor the selection process to their specific needs, resulting in higher quality candidates. However, the research also identified several challenges, such as the need for accurate data, potential bias in algorithms, and the need for ongoing monitoring to ensure transparency and fairness in the recruitment process. AI offers an effective solution to improve efficiency and accuracy in recruitment and selection, but successful implementation requires a deep understanding of the technology as well as a commitment to minimizing risk and ensuring a fair and transparent process.